Spectrophotometric Estimation of Olmesartan Medoxomil and Metoprolol Succinate in Tablet Dosage Form by Zero Order Derivative and Area Under the Curve Method - Ahmed, Faiz; Das, Rina; Mehta, Dinesh Kumar; Patel, Samir; Patel, Archita (Indian Journal of Pharmaceutical Education and Research)
Background: Olmesartan Medoxomil (OLM) and Metoprolol succinate (MET) formulations treat hypertension. The primary goal was to develop and evaluate a UV-spectrophotometric method for simultaneous estimation of OLM and MET in a combination tablet dosage form by ICH standards. Aim: The study aimed to develop a simple, swift, precise, accurate and cost-effective UV spectrophotometric method for the area under curve and zero-order method of OLM and MET in a combined tablet dosage form using distilled water as solvents. Materials and Methods: Using distilled water as solvents the approach is predicated on zero order equation. OLM has an absorbance maximum at 255 nm, while MET is at 215.5 nm in the zero-order equation. OLM had an absorbance maximum between 265-250 nm, while MET was 219-205 nm, as determined by the area under curve method. The suggested approach’s reliability, precision, specificity, toughness and robustness were verified. Beer’s rule was followed by OLM and MET between 2-10 μg/mL for both, respectively, with a correlation coefficient value is 0.999. Results: Recovery experiments determined the accuracy of all methods and revealed recoveries between 99-101%. Interday and intraday precision were evaluated and the mean %RSD for all approaches was less than 2%. Conclusion: This study demonstrates that all parameters, including precision, recovery, accuracy and robustness, were met by ICH guidelines. The analysis’s findings have been scientifically and statistically validated. Therefore, it can be stated that the approach was novel, easy to implement, selective and specific in its ability to estimate both OlM and MET in bulk powder.
Keywords: Area under curve; Distilled water; Metoprolol succinate; Olmesartan medoxomil; Validation; Zero-order spectrophotometry.